Thermo-economic optimization of an organic Rankine cycle system for large marine diesel engine waste heat recovery. (15th March 2015) - Yang, Min-Hsiung; Yeh, Rong-Hua
Abstract: The thermo-economic optimization of an ORC (organic Rankine cycle) used to recover waste heat from large marine diesel engines are conducted numerically. The variations of net power output, thermal efficiency, and total cost of equipments of the ORC system with various turbine inlet and outlet pressures are investigated. The net power output index is first proposed to evaluate the performance for this waste heat recovery system. To consider the environmental protection, working fluids which are zero ozone depletion potential and low global warming potential are selected in the simulation of the ORC system. For the widely-used working fluid, R245fa, an improvement of 6% in thermal efficiency is obtained for the proposed system compared with the ORC system recovering heat from marine diesel engine. The results show that, among these working fluids, R1234yf performs the best in the optimal thermo-economic performance evaluation, followed by R1234ze, R152a, and R600a; R245fa performs the least favorably. In addition, the maximal thermo-economic performance of the presented ORC system with R1234yf is higher than that with R245fa by 9%. Finally, the calculated corresponding optimal thermal efficiency of the ORC system and turbine inlet and outlet pressures of working fluids are obtained and compared. Highlights: The maximal thermal-economic performance of an ORC is conducted. R1234yf performs best, followed by R1234ze, R152a, R600a, and R245fa performs the worst. Increasing turbine inlet temperature of working fluid improves the economic performance. Cooling water temperature affects the optimal high pressure more strongly than lower pressure.